Expert opinion on continuous rhythm monitoring of patients with atrial fibrillation for candidates or patients who have already undergone ablation. (15th April 2020) - Palmisano, Pietro; Del Greco, Maurizio; Mantica, Massimo; Moltrasio, Massimo; Pecora, Domenico; Pisanò, Ennio C.L.; Rovaris, Giovanni; Perego, Giovanni Battista
Abstract: Background: Continuous monitoring by implantable loop recorder (ILR) can provide information relevant to rhythm control and oral anticoagulation (OAC) after atrial fibrillation (AF) ablation, but there is little agreement on patients' selection and appropriate management strategy. Methods: An expert panel (EP) made up of eight Italian electrophysiologists with expertise in AF ablation, gathered to define an algorithm to guide continuous rhythm monitoring in AF patients who have undergone ablation. The process included a review of the current literature and two EP face-to-face meetings. Between the two meetings, an on-line survey was sent to 50 Italian electrophysiologists practicing AF ablation. Agreement level was considered reached when ≥70% of respondents agreed or were neutral. Results: Two algorithms were developed to define patients for whom the ILR would be suggested support for (OAC) therapy discontinuation and rhythm management after AF ablation. Thirty-three out of 50 physicians responded to on-line survey (66% response rate). Together with EP members the responders accounted for electrophysiology centers performing about 50% of total yearly Italian AF ablation procedures. Agreement level was reached at the first survey round on all the questions, so the algorithms were not further modified and re-tested. Conclusions: EP developed two algorithms for ECG monitoring to guide OAC therapy discontinuation and rhythm management after AF ablation. These suggestions, validated by wide feedback and consensus of physicians performing AF ablations, might support the decision on the choice and the use of ECG monitoring techniques, based on specific patient characteristics. Highlights: There is a low correlation between AF episodes and symptoms. Implantable Loop Recorder (ILR) is seldom used for AF detection after ablation. An Expert Panel developed two algorithms for ILR use after AF ablation. The two algorithms were validated by 33 electrophysiologists. These suggestions might support the decision to use ILR after AF ablation.